School anxiety of children with severe bronchial asthma - Bogutska, Nataliia; Сhepura, Oksana (Psychosomatic Medicine and General Practice, 2021)
This text is the thesis of a distance report to the III scientific-practical conference with international participation "Psychosomatic medicine: science and practice". The following is dedicated to school anxiety of children with severe bronchial asthma.